Advanced Imaging of Traumatic Brain Injury - Lee, A Leum (Korean J Neurotrauma, 2020)
Traumatic brain injury (TBI) is a major health and socio-economic problem worldwide that mainly affects young adults. Neuroimaging plays a critical role in the diagnosis and evaluation of patients with TBI. Some patients with mild TBI have variable neurological symptoms. In such patients, computed tomography and magnetic resonance imaging (MRI) can present normal findings. Advanced imaging techniques, such as diffusion tensor imaging, magnetic resonance spectroscopy, perfusion weighted imaging, or functional MRI, can reveal abnormalities that are not detected using conventional imaging methods. Here, I briefly review current neuroimaging for TBI and survey advanced imaging techniques in terms of structural and functional aspects, which include a few promising areas of TBI research.